We shall overcome : the story of a song - Levy, Debbie; Brantley-Newton, Vanessa (New York : Disney/Jump at the Sun Books, 2013)
Traces the history of the inspiring anthem and explains how it has come to represents the right for equality and freedom around the world.
Includes bibliographical references (page 32).
Keywords: We shall overcome -- Juvenile literature; Protest songs -- United States -- Juvenile literature; African Americans -- Civil rights -- Juvenile literature; We shall overcome; Protest songs; African Americans -- Civil rights